Safety and Liability for Accidents on Ski Slopes – An Overview of Regulations, Rules, Statistical Data, and Selected Case Law - Flander, Benjamin (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
Skiing and snowboarding are among the most popular winter sports and represent an important component of the sports and tourism industry in Alpine and other mountainous regions. Despite significant advances in infrastructure, supervision, and preventive measures, accidents on ski slopes remain relatively frequent. This article examines legal regulation of safety on Slovenian ski slopes and the legal consequences of accidents arising from (recreational) skiing and snowboarding. The analysis focuses on the relevant legal framework, the rules of the International Ski and Snowboard Federation (FIS), and statistical data on accidents, as well as selected case law to illustrate how courts interpret standards of due diligence and responsibilities of ski slope operators, and the obligations of individual skiers and snowboarders. Particular attention is devoted to obligatory insurance in addressing the consequences of ski and snowboard accidents.